TINDAK PIDANA CYBER BULLYING DALAM PERSPEKTIF HUKUM PIDANA DI INDONESIA - Saprudin Hamdani; Ariy Khaerudin; Hanuring Ayu Ardhani Putri (LP3M, 2022)
Information technology is one of the most rapidly developing needs in this modern era. As a result of these developments, information technology gradually changes the behavior of people and human civilization globally. The development of this technology also has an impact in the world of crime, namely the existence of a type of humiliation that is insulted through cyberspace called Cyber Bullying. This study aims to determine the regulation of cyber bullying in terms of the Criminal Code and outside the Criminal Code. This study uses a normative juridical research method with a statutory approach and a conceptual approach. The results of the writing of this journal show that the regulation of cyber bullying in terms of the Criminal Code can be seen in Article 315 of the Criminal Law Code because the cyber bullying crime fulfills both the subjective and objective elements contained in the article. Furthermore, the regulation of cyber bullying outside the Criminal Code Act is contained in Article 27 Paragraph (3) of Law No. 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions because it explains in the article regarding insults committed through computer or electronic media which are in accordance with cyber bullying which is an insult through cyberspace